Evaluation of a pregnancy loss education intervention for undergraduate nursing students in Northern Ireland: A pre- and post-test study - Martina Galeotti; Suzanne Heaney; Martin Robinson; Áine Aventin (BMC, 2023)
Abstract Background Research highlights the importance of compassionate communication, adequate delivery of information, and professional support to help alleviate parental distress following pregnancy loss. However, many healthcare professionals do not feel sufficiently trained to deal with pregnancy loss in practice. We aimed to address this deficiency with an evidence-informed educational intervention to increase knowledge, skills, self-awareness, and confidence regarding pregnancy loss among UK nursing students. Methods Educational resources, which included an 82-minute podcast and 40-minute online lecture were developed. The podcast focused on the lived experiences of three women who had experienced miscarriage, stillbirth, and termination of pregnancy for medical reasons. The pre-recorded lecture included definitions of types of pregnancy loss, discussion of the importance of communication, and information on the clinical management of pregnancy loss. Students were presented with both the lecture and podcast as a self-directed element of existing curricula. A pre-test/post-test cross-sectional survey design was used to investigate the impact of the educational intervention. The Perinatal Bereavement Care Confidence Scale (PBCCS) was completed by 244 first year BSc Nursing students before and up to a week after receiving the intervention. Quantitative data were analysed using a Paired Samples Wilcoxon test. Responses to open-ended questions, which allowed students to give feedback on the intervention content and delivery were analysed using Qualitative Content Analysis. Results 96% (n = 235) of the sample reported having no prior experience or training in the management and support of those experiencing pregnancy loss. At pre-test, 88% (n = 215) of students rated themselves as not confident in dealing with pregnancy loss in a professional capacity. Post-test, we found statistically significant effects for perceived competency on all learning outcomes (p < .001). Qualitative analysis of n = 745 individual text responses to open-ended questions indicated four categories related to the perceived value of using real-life stories for learning, demystifying a taboo subject, and providing tools for practice. Respondents suggested the inclusion of more information on memory-making, support networks, and mental health following pregnancy loss. Conclusions The educational intervention increased student nurses' perceived knowledge, confidence, and skills in caring for families experiencing pregnancy loss. This offers potential for increased quality of care for those experiencing pregnancy loss in healthcare settings, increased patient satisfaction, and improved mental health-related outcomes.